2021
DOI: 10.1002/jbt.22701
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate and coenzyme Q10 attenuate cisplatin‐induced hepatotoxicity in rats via targeting mitochondrial stress and apoptosis

Abstract: Despite the extensive use of cisplatin (CP) as a chemotherapeutic agent, its clinical use is often restricted by undesirable side effects, such as toxicity to normal tissues. The aim of this study was to probe the effect of a combinatorial treatment of low multiple doses of antioxidants on CP‐induced toxicity and the mitochondrial apoptotic pathway in hepatocytes. Animals received a single toxic dose of CP (7.5 mg/kg body weight) with or without combined multiple doses of epigallocatechin gallate (EGCG) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…EGCG treatment decreases hepatic lipid peroxides and carbonyl formation, reducing oxidative stress [ 20 ]. Antioxidant enzymes increases after administration of EGCG in rats [ 14 , 23 ]. EGCG administration can regulate cell apoptosis by interfering with oxidative stress mechanisms (the most important mechanism revealed by experimental studies in vivo was represented by the ability to induce endogenous antioxidant systems) [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…EGCG treatment decreases hepatic lipid peroxides and carbonyl formation, reducing oxidative stress [ 20 ]. Antioxidant enzymes increases after administration of EGCG in rats [ 14 , 23 ]. EGCG administration can regulate cell apoptosis by interfering with oxidative stress mechanisms (the most important mechanism revealed by experimental studies in vivo was represented by the ability to induce endogenous antioxidant systems) [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alqarni et al reported that co-administration of CoQ10 with valproic acid in epilepsy not only increases the antiepileptic activity, but also reduces the hepatotoxicity of valproic acid (45). Furthermore, Fatima et al confirmed protective effects of CoQ10 against cisplatin-induced hepatotoxicity in animals (46).…”
Section: Discussionmentioning
confidence: 98%
“…( 2018 ) and Fatima et al. ( 2021 ) who stated that CoQ10 inhibited the activation of caspase-3 and the release of cytochrome c from mitochondria via stabilizing the mitochondrial membrane, thus preventing the release of apoptotic mediators. El-Khadragy et al.…”
Section: Discussionmentioning
confidence: 99%